Employing SysML to model and explore levels‐of‐service: The case of passenger comfort in railway transportation systems. Issue 1 (29th August 2019) - Kotronis, Christos; Nikolaidou, Mara; Kapos, George‐Dimitrios; Tsadimas, Anargyros; Dalakas, Vassilis; Anagnostopoulos, Dimosthenis
Abstract: The concept of Level of Service (LoS) is not inherently supported by Systems Modeling Language (SysML), the standard modeling notation for model‐based systems engineering. This paper describes and demonstrates an approach that enhances SysML to enable LoS modeling and evaluation. A SysML profile enables the definition and visual verification of LoS during system operation, via LoS specific requirements, inside the system model, and the association of these requirements with specific system components. Hence, static and dynamic aspects of the system model are used for the LoS verification, while specific design alternatives are automatically proposed, in case the desired LoS is not achieved. As a proof of concept, the proposed approach was applied to explore passenger comfort, a key LoS metric, indicating space available to passenger in Railway Transportation Systems (RTSs). A specific case study on passenger comfort for the Athens Metro was conducted to derive insights regarding the practical aspects of the proposed approach.